2009
DOI: 10.4070/kcj.2009.39.10.423
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences Among Korean Patients With Coronary Spasm

Abstract: Background and ObjectivesThe gender differences among Korean patients with coronary spasm have not been defined. We thus determined the gender differences among Korean patients with coronary spasm.Subjects and MethodsPatients with chest pain and/or syncope who were admitted to Kyungpook National University Hospital between January 2001 and August 2008 were included. Provocation of coronary vasospasm with intracoronary ergonovine maleate was performed when baseline coronary angiography showed no significant ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In the present study, we found that there were more male patients with chest pain who experience coronary artery spasm after provocation, compared with female patients, which fits with previous reports from Japan and Korea . Coronary artery spasm may occur more frequently in males than in females and may be a male dominant disorder.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found that there were more male patients with chest pain who experience coronary artery spasm after provocation, compared with female patients, which fits with previous reports from Japan and Korea . Coronary artery spasm may occur more frequently in males than in females and may be a male dominant disorder.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that a history of smoking was significantly more frequent in males than in females in our population. It has previously been reported that smoking was the most important risk factor for coronary artery spasm . In animal models, cigarette smoke extract causes endothelial dysfunction by reducing NO activity .…”
Section: Discussionmentioning
confidence: 99%
“… 77 Studies are conflicting on prevalence by sex – some studies have shown it is more common in women. 78 , 79 In one study, outcomes were worst in young females presenting with coronary vasospasm. 80 Treatment includes calcium channel blockers and nitrates.…”
Section: Introductionmentioning
confidence: 99%
“…VA is also caused by the functional abnormalities of the coronary artery; however, sex differences in VA have not yet been well studied. In particular, VA is highly prevalent in males [ 1 , 2 ], and there has been limited data on the characteristics of female patients with VA. Until now, only a few studies have addressed sex difference in VA [ 13 17 ]. Among these studies, only two studies have investigated sex differences in long-term VA prognosis; however, sex-specific factors determining long-term clinical outcome of VA are inconsistent [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%